2021
DOI: 10.1109/access.2021.3083531
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Turbulent Flow of Water Optimization on Economic Load Dispatch Problem

Abstract: The economic load dispatch (ELD) problems considering nonlinear characteristics where an optimal combination of power generating units is selected in order to minimize the total cost by economic allocation of power produced and the emission cost. As a consequence, optimal allocation is performed by considering both fuel cost and emission leading to Combined Economic and Emission Dispatch (CEED). This study presents a new Meta-heuristic algorithms (MHs) called the Turbulent Flow of Water Optimization (TFWO), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Even though the original snake dataset is limited, they could attain consistent results. Alsing et al [47] created genuine CNN infrastructure based on domain adaptation to detect post-it locations and then converted these algorithms to be used on smartphones and tablets. The fastest RCNN ResNet50 structure had the highest MAP (mean average precision) of 99.33%, but it took 20,018 milliseconds to infer.…”
Section: Related Workmentioning
confidence: 99%
“…Even though the original snake dataset is limited, they could attain consistent results. Alsing et al [47] created genuine CNN infrastructure based on domain adaptation to detect post-it locations and then converted these algorithms to be used on smartphones and tablets. The fastest RCNN ResNet50 structure had the highest MAP (mean average precision) of 99.33%, but it took 20,018 milliseconds to infer.…”
Section: Related Workmentioning
confidence: 99%
“…According to the papers described above, deep learning architectures are rapidly being applied to facemask detection to prevent COVID-19 spread using a transfer learning-based deep neural network [27][28][29][30][31][32][33][34]. Other deep learning [35][36][37][38][39][40][41][42] and optimization algorithms are also used to solve various optimization problems [43][44][45][46][47][48][49][50][51]. However, several gaps in using deep learning systems for real-time implementation and prevention strategies must be addressed, as indicated [52][53][54][55][56][57].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [17], authors have proposed an enhanced version of Jaya algorithm incorporating multiple population and Levy flight for solving ELD and CEED. In [18], authors validated the performance of Turbulent Flow of Water Optimization (TFWO) algorithm on ELD and CEED and concluded that the algorithm is as competitive as other state of art metaheuristics. In [19], the authors proposed a Chameleon Swarm Algorithm (CSA) mimicking the behaviour of chameleons for solving ELD and CEED.…”
Section: Introductionmentioning
confidence: 99%